Studi Tentang Kompetensi Guru PAUD Berkualifikasi Akademik Sarjana PG-PAUD Dan NonPG-PAUD di PAUD Istiqomah Sambas Purbalingga - Yuslam, Yuslam; Setiani, Riris Eka; Sari, Almi Kurnia (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2017)
Through this research the author attempt to explore and examine how pedagogic competence and professional competencies Early Childhood teachers academics qualified beetwen S1 PG -PAUD and non PG-PAUD. This research type is field research. The data collection method using the interview, observation and communication. the data analysis using the data reduction technique, presentation of data and conclusions. The results of this research showed that the teachers who have competency S1 PG-PAUD appear to have sufficient understanding of the development of the children. The understanding of the development implicated against the election of learning materials and the use of learning methods that adjusted with the developmental stage. It is different with teachers nonPG-PAUD, they appear to not understand the developmental stage until there from some teachers who use the method less in accordance with the children development. the differences also appear in the case of mastering, making lesson plans and learning evaluation. As part of the effort to improve teachers Profesionalism, the institutions apply some policy Including: selective recruitment, internship program for six months, guidance careers, develop training programs, sharing between teachers and provide the opportunity for teachers S1 nonPG-PAUD to lectures S1 PG-PAUD Education.